2023
DOI: 10.1530/ec-22-0464
|View full text |Cite
|
Sign up to set email alerts
|

Treatment burden, adherence, and quality of life in children with daily GH treatment in France

Abstract: Objective: To describe in a real-life setting the treatment burden and adherence, and quality of life of children treated with daily injections of growth hormone, and their relationship with treatment duration. Design: This non-interventional, multicenter, cross-sectional French study involved children aged 3 to 17 years treated with daily growth hormone injections. Methods: Based on a recent validated dyad questionnaire, the mean overall Life Interference total score (100=most interference) was described, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Parents also faced some challenges in terms of maintaining a consistent treatment schedule. This was especially true where parents wanted to travel, or with older children who took part in more activities evident in previous research amongst families administering growth hormone treatment [13][14][15][16]. This is something which will likely become more important in the future, as parents continue treatment over the course of years and seek to travel more and have a normal life.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Parents also faced some challenges in terms of maintaining a consistent treatment schedule. This was especially true where parents wanted to travel, or with older children who took part in more activities evident in previous research amongst families administering growth hormone treatment [13][14][15][16]. This is something which will likely become more important in the future, as parents continue treatment over the course of years and seek to travel more and have a normal life.…”
Section: Discussionmentioning
confidence: 93%
“…This contrasts with previous research in similar areas [ 14 , 16 ]. Parents may be especially committed to persisting through challenges and identifying strategies for reducing burden to both themselves and their children given the lack of alternative treatment options [ 15 ]; however, this is a hypothesis which warrants further investigation. As in previous research, parents reported a reduction in barriers over time as the family adjusts to treatment [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation